A city walkable: [Re]Imagining spatial justice through access and public space in North End, East London - Hendricks, Lerys (School of Architecture, Planning and Geomatics, 2023)
A city walkable is about re-imagining spatial justice through access and public space in North End, East London, South Africa. The research questioned the state of East London's public space, its inner-city decay, and its vehicular dependency. East London lacks good quality public space that is walkable and accessible. A city walkable has streets that are comfortable, safe, interesting and offer choice. The urban environment must foster walkability. Before Apartheid, North End was a mixed-race community that was spatially integrated with the city because of its proximity to the CBD and its urban fabric. North Enders never needed to own a vehicle to access amenities. People could access their everyday amenities on foot and felt safe walking day or night. North End was a walkable, mixed-use neighbourhood. However, due to the Group Areas Act of 1950, people were forcibly removed from the city and relocated to what is now known as townships. Due to this removal people are forced to rely on public transport or private vehicle for mobility. Townships are not mixed-use, and streets do not foster walkability. By removing people from the city, Apartheid removed walkability. The fundamentals of living in a city are access to the convenience of amenities and work. Denying access to the city is a spatial injustice. This denial has resulted in a lack of walkable streets, unsafe public spaces, and car dependency. Since the forced removals of 1950' North End has been rezoned as a light industrial area. The research aimed to unlock the potential for walkability in East London. North End is re-imagined not only a walkable neighbourhood, but as a neighbourhood that is integrated with both township areas and the CBD. The links used to create linkages are a series of urban mixed-use corridors. Thus, creating a city that is spatially just. This makes North End a strategic place in the city which has the potential to become East London's 'knuckle'. Through various interventions, spatial strategies, and framework a more just, walkable city is envisioned.